From Text to Sermon Responsible use of the New Testament in preashing - Best, Ernest (Atlanta John Knox Press, 1978)
Best identifies the most common problems facing anyone who seeks to interpret the New Testament. He then shows how the preacher, teacher or ordinary reader can faithfully draw out the meaning of the New Testament.
Keywords: Preaching. Bible. -- New Testament -- Hermeneutics. Bible. -- New Testament -- Theology. Bible. -- New Testament. -- Hermeneutics. Bible. -- New Testament. -- Theology. Bible. -- New Testament. Hermeneutics. Theology